Iot-enabled integrated health monitoring system: real-time data collection and analysis for improved chronic disease management and reducing poverty - Ali, Abdifatah Farah; Abdullah, Rusli; Abi Hassan, Abdikarim; Abdullahi, Husein Osman (Seventh Sense Research Group, 2024)
Healthcare monitoring systems are innovative technologies that facilitate real-time patient data tracking and analysis, enabling remote monitoring, personalized treatment, and improved diagnosis. These technologies increase productivity and efficiency and reduce costs, attracting global interest due to their potential benefits. Internet of Things (IoT) technology has transformed healthcare, shifting from in-person consultations to telemedicine. An IoT-based smart healthcare system that monitors a patient's vital health indicators and room environment in real-time is proposed in this study. Data is collected using five IoT sensors, including a heart rate sensor, a body temperature sensor, a room temperature sensor, a carbon monoxide sensor, and a carbon dioxide sensor. The error margin for each parameter is less than 5%. Patient situations are provided to medical professionals via a gateway, allowing for real-time processing and analysis. The system's efficiency proves it is suitable for monitoring healthcare and is an invaluable tool in modern healthcare environments by its effectiveness.